Impak Faktor Insaniyyah dalam Pelaksanaan Sistem Pengurusan Kualiti Berasaskan Syariah MS 1900: Kajian di Institusi Pengajian Tinggi Islam Malaysia - Basir, Siti Arni; Mohamed, Hasan Al-Banna; Ali@Mat Zin, Aizan; Jalal, Burhanuddin (Jurnal Usuluddin, 2022)
The literature shows that previous studies on the implementation of Quality Management Systems have focused more on technical issues, while the study on insaniyyah factors has not been explored. The objective of this paper is to study the impact of insaniyyah factors in Syariah-Based Quality Management System MS 1900 implementation in Islamic-based Higher Education Institution in Malaysia. This qualitative study selected one Higher Education Institution located in the Klang Valley as the case study organization. Semi-structured interviews and document review were used as data collection methods in this present study. Research findings reveal there are five insaniyyah factors in the implementation of MS 1900, namely leadership, communication, student personality development, cooperation and reward. These insaniyyah factors have a positive impact because they have helped to the effective implementation of MS 1900 in the HEI studied. The findings of this study contribute to the development of knowledge regarding insaniyyah factors in the context of MS 1900 implementation since this topic has never been explored by previous researchers. The findings can be employed as a guide by administrators in HEIs and public or corporate organizations in their efforts to apply insaniyyah factors in the implementation of MS 1900 effectively in their respective organizations.